NATO Commander to Commander-in-Chief: the influence of Dwight Eisenhower's experiences as NATO Supreme Commander on the "New look" defense policy - Plocinski, Joshua R. (Kansas State University, 2008)
As the 1950s began, Western European defense policy posed unique challenges for the United States. At the outset of the Cold War, U.S. officials recognized that maintaining a free Western Europe was vital to the long-term survival of the United States against the Soviet Union and its satellite nations. While America could rely on its long-range nuclear bombers (and, in a few years, its intercontinental ballistic missiles) as a deterrent to Soviet aggression against the continental United States, the situation in Europe was more complicated. The North Atlantic Treaty Organization (NATO), first organized in 1949, was the defense pact designed to counter the Soviet Bloc in Eastern Europe. The NATO alliance, however, still recovering from the destruction of the Second World War, was in no condition to oppose Soviet aggression at the end of 1950. Yet by 1955, the situation in Europe was dramatically different. The NATO allies had transformed from a loose confederation of weak nations to a strong international alliance capable of confronting the Communist forces if necessary. At the center of this transformation was Dwight D. Eisenhower. In January 1951, Eisenhower assumed the position of NATO's first Supreme Allied Commander, Europe (SACEUR) and spent nearly two years strengthening the Western European alliance. Then, after entering the White House as president in 1953, Eisenhower used his experiences as SACEUR to reinforce several aspects of his own defense policy. Ultimately, several key aspects of Eisenhower's ―New Look‖ defense policy (such as the continued emphasis of the NATO alliance) had their antecedents in Eisenhower's service as NATO Supreme Commander.
Keywords: Eisenhower; SACEUR; History, United States (0337)